Carveol a Naturally-Derived Potent and Emerging Nrf2 Activator Protects Against Acetaminophen-Induced Hepatotoxicity - Rahman, Zaif Ur; Al Kury, Lina Tariq; Alattar, Abdullah; Tan, Zhen; Alshaman, Reem; Malik, Imran; Badshah, Haroon; Uddin, Zia; Khan Khalil, Atif Ali; Muhammad, Naveed; Khan, Saifullah; Ali, Amjad; et al. (Frontiers in Pharmacology, 2021)
Acetaminophen (N-acetyl p-aminophenol or APAP) is used worldwide for its antipyretic and anti-inflammatory potential. However, APAP overdose sometimes causes severe liver damage. In this study, we elucidated the protective effects of carveol in liver injury, using molecular and in silico approaches. Male BALB/c mice were divided into two experimental cohorts, to identify the best dose and to further assess the role of carveol in the nuclear factor E2-related factor; nuclear factor erythroid 2; p45-related factor 2 (Nrf2) pathway. The results demonstrated that carveol significantly modulated the detrimental effects of APAP by boosting endogenous antioxidant mechanisms, such as nuclear translocation of Nrf2 gene, a master regulator of the downstream antioxidant machinery. Furthermore, an inhibitor of Nrf2, called all-trans retinoic acid (ATRA), was used, which exaggerated APAP toxicity, in addition to abrogating the protective effects of carveol; this effect was accompanied by overexpression of inflammatory mediators and liver =2ltoxicity biomarkers. To further support our notion, we performed virtual docking of carveol with Nrf2-keap1 target, and the resultant drug-protein interactions validated the in vivo findings. Together, our findings suggest that carveol could activate the endogenous master antioxidant Nrf2, which further regulates the expression of downstream antioxidants, eventually ameliorating the APAP-induced inflammation and oxidative stress.